Scientific Background of Dairy Protein Digestibility: A Review - Shrestha, Ashok Kumar (Journal of Food Science and Technology Nepal, 2014)
Recent advances have shown that differences in compositional, structural and physical properties of caseins and whey proteins affect their digestion and absorption behavior, hormonal response, satiety effect and other physiological effects. For example, the ingestion of whey protein cause fast, high and transient increase of amino acids ‘fast protein’, whereas casein induce slower, lower and prolonged increase of ‘slow protein’ in the gut. Knowledge of, and control over, the rate and nature of digestive breakdown of dairy proteins provides a potential basis for product/process innovation through identifying ingredients and formulations that provide desired nutrient delivery profiles. With this background, the aim of our current review paper is to understand the digestion behavior of various protein-rich milk powders and their potential use in formulation of dairy foods for controlled release of amino acids and energy. Currently available in vitro protein digestibility methods to measure or predict the dairy protein digestibility were also investigated. The author has also presented the preliminary results of ongoing study on in vitro digestion of various commercial proteins powders. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10560 J. Food Sci. Technol. Nepal, Vol. 7 (1-8), 2012